User Acceptance of Online Examination System Using the Unified Theory of Acceptance and Use of Technology (UTAUT) Model - Ay, Mario Hendrial Christanto (Universitas Negeri Malang, 2023)
User acceptance is one of the factors that need to be considered in order to improve the quality of the online examination system. Therefore, an evaluation model is needed to measure online examination system user acceptance. The Unified Theory of Acceptance and Use of Technology (UTAUT) is one of the evaluation models used in this study. This study aims to determine the user acceptance of the web-based online examination system at Public VHS 4 Malang using the UTAUT factors. The UTAUT factors used are performance expectancy, effort expectancy, social influence, and facilitating conditions as exogenous latent variables, and behavioral intention as an endogenous latent variable. The respondents in this study were students in the 12th grade of 2022/2023 school year. The total number of students was 274. The data obtained were analyzed using the Partial Least Square (PLS) method using SmartPLS 3 software. In this study, performance expectancy, effort expectancy, and facilitating conditions have a positive and significant effect on behavioral intention, while social influence has a positive but insignificant effect on behavioral intention.